Effect of physical dental environment on the axiety of adult patients while in waiting areas of mall-based dental clinics in Alabang - Sarapuddin, Saada Mariz B.
INTRODUCTION: Anxiety is one of the documented reasons why people avoid seeking dental treatment. One method to manage dental anxiety is through physical environmental stimulation. The study aimed to determine the effects of the physical dental environment in waiting areas on the anxiety of adult patients prior to treatment.